Impact of Hempseed Incorporation on the Quality Characteristics of Granola: Nutritional and Sensory Evaluation - Wazir, Asma; Murtaza, Ayesha; Shaukat, Iqra; Fatima, Itrat; Fatima, Eman; Shahid, Fatima; Noor, Aimen; Karim, Fazal; Ali, Asad (Biological and Clinical Sciences Research Journal, 2025)
Health-conscious consumers are increasingly seeking functional foods enriched with natural ingredients to promote wellness. Hemp seeds, a nutrient-dense byproduct of commercial fiber production, offer potential for incorporation into food products to enhance both nutritional and sensory attributes. Objective: This study aimed to develop hempseed-incorporated granola using two different processing techniques and to evaluate its nutritional composition, functional properties, and sensory acceptability. Methods: A comparative experimental study was conducted to prepare hempseed-based granola using oven-baked and roasted methods. Proximate composition (moisture, ash, fat, fiber, protein, carbohydrate), functional properties (bulk density, oil-holding capacity, water-holding capacity, swelling index), and sensory evaluation (taste, color, aroma, texture, mouthfeel, overall acceptability) were assessed. Data were analyzed using standard statistical procedures to determine significant differences between treatments (p<0.05). Results: The oven-baked granola demonstrated significantly higher ash (2.68%), fat (22.47%), fiber (5.52%), and protein (16.45%) contents, whereas roasted granola contained higher moisture (4.30%) and carbohydrate (56.17%) levels. Functional characteristics were improved in the oven-baked product, including bulk density (1.00), oil-holding capacity (2.85), water-holding capacity (2.19), and swelling index (3.60). Sensory scores indicated superior consumer acceptance for the oven-baked granola in terms of taste, color, aroma, texture, mouthfeel, and overall acceptability compared with roasted granola. Conclusion: Incorporating hempseed enhances the nutritional, functional, and sensory qualities of granola, particularly when processed using oven-baking methods. This product provides a sustainable and health-promoting snack alternative for individuals pursuing nutritious and natural dietary options.